2021
DOI: 10.1093/jaoacint/qsab098
|View full text |Cite
|
Sign up to set email alerts
|

LC-ESI-MS/MS Simultaneous Analysis Method Coupled with Cation-Exchange Solid-Phase Extraction for Determination of Pyrrolizidine Alkaloids on Five Kinds of Herbal Medicines

Abstract: Background Pyrrolizidine alkaloids (PAs) are naturally occurring plant toxins associated with potential hepatic and carcinogenic diseases in humans and animals. The concern of PAs has been increased as the consumption of herbal medicines is increased. Objective This study aimed to develop and validate a sensitive analytical method to determine 28 PAs in 5 herbal medicines using liquid chromatography-electrospray ionization ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The results revealed that the majority of herbal samples did not contain any of the 28 pyrrolizidine alkaloids. However, in the case of Leonuri Herba, retrorsine was identified within a concentration range of 84.7–120.9 μg/kg, and senkirkine was consistently present in all Leonuri Herba samples, with concentrations ranging from 60.9 to 170.7 μg/kg 96 …”
Section: Analytical Approaches For Estimation Of Alkaloidsmentioning
confidence: 90%
See 1 more Smart Citation
“…The results revealed that the majority of herbal samples did not contain any of the 28 pyrrolizidine alkaloids. However, in the case of Leonuri Herba, retrorsine was identified within a concentration range of 84.7–120.9 μg/kg, and senkirkine was consistently present in all Leonuri Herba samples, with concentrations ranging from 60.9 to 170.7 μg/kg 96 …”
Section: Analytical Approaches For Estimation Of Alkaloidsmentioning
confidence: 90%
“…However, in the case of Leonuri Herba, retrorsine was identified within a concentration range of 84.7-120.9 μg/kg, and senkirkine was consistently present in all Leonuri Herba samples, with concentrations ranging from 60.9 to 170.7 μg/kg. 96 Pyrrolizidine alkaloids from herbal teas were detected using LC- 97 Klein and coworkers developed an LC-MS/MS method for the determination of pyrrolizidine alkaloids in cow milk samples. They extracted 51 pyrrolizidine alkaloids and two tropane alkaloids from 15 different cow milk samples.…”
Section: Pyrrolidine Alkaloidsmentioning
confidence: 99%
“…That is, when there is a matrix effect, linearity should be evaluated using a standard solution containing the sample matrix [36]. Matrix effect can be classified as strong matrix effect below 50% or above 150%, moderate matrix effect between 50-80% or 120-150%, and low matrix effect between 80-120% [37]. Taking the criteria into account, the matrix effect on 8 PAHs was investigated.…”
Section: Matrix Effectmentioning
confidence: 99%
“…The calibration curves were achieved from seven-point concentrations ranging from 1 to 100 ng/mL. The matrix effect was evaluated by the following formula [37]: Matrix effect (ME, %) = (slope of the calibration curve in matrix/slope of the calibration curve in solvent) × 100.…”
Section: Matrix Effectmentioning
confidence: 99%
“…The preconcentration-extraction-based techniques are still in significant use to make analytes available for sensitive measurements [11]. Among them, SPE is also frequently used to preconcentrate the target compound from plant materials that has been reported in many studies [12,13]. A small quantity of target compound from a highly complex phytochemical composition of plant samples could be preconcentrated prior to analytical determination [14].…”
Section: Introductionmentioning
confidence: 99%